Monkeypox infection in pregnancy, maternal and fetal outcomes: a systematic review - Camones-Huerta, Jose; Cordero-Campos, Alexander; Cuya-Sahua, Alheli; Guzmán-Carrasco, Susana; Condori-Quispe, Leslie; Chin-Wu, Karina; Quispe-Villegas, Gustavo; Flores-Noriega, Mónica (The Journal of Infection in Developing Countries, 2025)
Introduction: Monkeypox (mpox) is an emerging infectious disease with increasing global incidence. Limited evidence exists regarding its impact on pregnancy and perinatal outcomes, especially in low-resource settings. The objective was to systematically synthesize current evidence on maternal and fetal outcomes associated with mpox infection during pregnancy. Methodology: A systematic review was conducted following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. PubMed, Scopus, Web of Science, and Embase (as of 4 September 2024) databases were searched. Case reports, case series, cohorts, and observational designs were included. Duplicates were removed using Rayyan. Only 6 studies (out of 471) met the eligibility criteria. A descriptive analysis was conducted due to heterogeneity and small sample sizes. Results: A total of 6 studies were included (4 from US, 1 from Spain, 1 from Democratic Republic of Congo), comprising 33 pregnant women aged 18–29 years. Mpox was confirmed by polymerase chain reaction (PCR) in 32 cases. The clinical symptoms included vesicular rash, genital lesions, and systemic manifestations. No maternal deaths were reported. Adverse fetal outcomes included miscarriage (9.1%), stillbirth (6.1%), and 4 intrauterine deaths. Most pregnancies (84.8%) resulted in live births. The reported complications included oligohydramnios, cholestasis, chorioamnionitis, and fetal tachycardia. One study confirmed vertical transmission via placental and fetal tissue analysis. Conclusions: Mpox infection during pregnancy is associated with significant risk of adverse perinatal outcomes. Although current evidence is limited, these findings highlight the urgent need for more robust data to inform clinical and public health guidance.